Expression of the X-CGD gene during induced differentiation of myeloid leukemia cell line HL-60. - Barker, K A (1988)
The expression of the X-CGD gene, which encodes the heavy-chain subunit of the phagocyte cytochrome b, was studied during induced myeloid differentiation of HL-60 cells. Incubation of the cells with a combined regimen of retinoic acid and dimethyl formamide resulted in granulocytic morphological differentiation and acquisition of nitroblue tetrazolium reduction, a measure of superoxide generation. During the 5-day course of induced differentiation, the levels of X-CGD mRNA transcripts rose 13-fold, with a 2-fold increase detectable within 3 h of exposure to retinoic acid. Relative transcription rates for the X-CGD gene, determined by nuclear runoff, increased two- to eightfold after 24 to 72 h of induced differentiation. However, the greater change in X-CGD mRNA levels than that in transcription rates implies the involvement of posttranscriptional regulation as well. Fractionation by centrifugal elutriation into phases of the cell cycle showed expression of X-CGD transcripts predominantly in G1 cells before induction and in all phases of the cell cycle 24 h after induction. Thus the rapid increase in X-CGD expression in induced cells reflects the acquisition of functional competence and not the concomitant cessation of proliferation or shift in cell cycle distribution.